Досвід країн світу плануванні та веденні особистих (сімейних) бюджетів - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Сіренко, Н. М.; Sirenko, N.; Мікуляк, К. А.; Mikuliak, K. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
Авторами статті дослідженні переваги і недоліки планування особистих (сімейних) бюджетів зарубіжних країн.Також в статті розкрито основні аспекти до організації ведення особистого (сімейного) бюджетування. В процесідослідження розглянуто міжнародний досвід організації особистих бюджетів, визначено типи сімейних фінансів, а також сучасні підходи до планування бюджету в різних країнах світу. Проаналізовано ключові моделі бюджетування, зокрема японську систему "какеібо", американську концепцію "50/30/20", європейські традиції ощадності та скандинавський підхід до фінансової рівноваги. Особливу увагу авторами приділено ролі фінансової грамотності, державних програм підтримки домогосподарств та цифрових інструментів управління бюджетом. На основі проведеного аналізу зроблено висновки щодо доцільності запозичення кращих міжнародних практик для підвищення ефективності ведення особистого бюджету в Україні. The financial behavior of the population is directly related to the widespread budgeting models and the general financial culture in the country. The more conscious and systematic the approaches to financial management, the higher the level of savings and stability of households. For Ukraine, a combination of educational initiatives with elements of the most effective international models is promising. The authors of the article study the advantages and disadvantages of personal (family) budget planning in foreign countries. The article also reveals the main aspects of organizing personal (family) budgeting. In the process of the study, the international experience of organizing personal budgets was considered,types of family finances were identified, as well as modern approaches to budget planning in different countries of theworld. Key budgeting models were analyzed, in particular the Japanese "kakeibo" system, the American concept of "50/30/20", European traditions of thrift and the Scandinavian approach to financial balance. The analysis shows that traditionsof thrift and budgeting models significantly influence the financial behavior of the population. The Japanese system of"kakeibo" promotes conscious spending, the American model of "50/30/20" - structured planning, and European andScandinavian approaches - high levels of savings. The implementation of effective budgeting models can contribute tofinancial stability and well-being of citizens. The international experience of European, American, Japanese andScandinavian budgeting concepts in the development of personal finances in Ukraine was taken into account. The authorspaid special attention to the role of financial literacy, state programs to support households and digital budget managementtools. Based on the analysis, conclusions were drawn on the feasibility of borrowing best international practices to increasethe efficiency of personal budgeting in Ukraine. Successful personal budgeting is closely linked to financial education.Public policy, access to technology, and cultural habits have a significant impact. Systems that combine digital solutions,educational initiatives, and community-based support are considered the most effective.
Experience of countries aro und the world in planning and managing personal (family) budgets
Keywords: фінансове планування; financial planning; особисті фінанси; personal finance; бюджетування; budgeting; цифрові програми; digital apps; фінансова грамотність; financial literacy